Fore Karst a biotope-focused planning approach for the ecological management of Susong Dalaga, Qurino - Lavilla, Dave O.; Palarca, Honorio T. (Quezon City College of Architecture, University of the Philippines Diliman, 2020)
It can be seen throughout history that the making of several existing cities through conventional planning approaches that prioritize built-up areas and rapid urbanization in the name of economic growth and social security, rather than protecting the environment and the ecological services it provides, have consistently been ineffective in maintaining sustainability. With this, there is a budding growth of a need to shift from the conventional to a greener approach. The research argues that the ecological management approach is a viable and greener approach to protect the ecological integrity of the landscape, especially in biotopes where ecological services are sought-after, such as the karst system Susong Dalaga found in Cabarroguis, Quirino Province. This is done by identifying the different biotopes in and
surrounding Susong Dalaga, in order to find the existing relations, services, and underlying issues of the place. In the assessment of the aforementioned items, the research finds that the natural systems are slowly dwindling due to the expansion of of agriculture and built-up areas. Each biotope are then assigned with an appropriate approach, and with the consultation of the constituents, policies can be strategized for specific functions. It hopes that the study would help push the application and integration of ecological management approach, and green approaches and principles in general, to future urban planning projects in the Philippines.
Thesis (Bachelor of Landscape Architecture) -- University of the Philippines Diliman
Keywords: Landscape ecology -- Susong Dalaga (Quirino).; Policy sciences -- Susong Dalaga (Quirino).; City planning -- Susong Dalaga (Quirino).